Learning in Transnational Environment. Reconstruction of Meanings Given to Learning by Foreign Students in Poland - Popow, Monika (INSTED: Interdisciplinary Studies in Education & Society, 2017)
The aim of the paper is to present results of a research project ?Learning in a transnational environment?, devoted to the meanings of learning given by international students in Poland. The phenomenographic method was used in the research project. Five dominating meanings were established, illustrating how individual experience of learning as well as collective and national experience may be connected in the learning process. In terms of theoretical framework, the notion of transnationalism, most of all related to the global changes in the Academy, was used.